(untitled) (Kriminalističke teme, 2007)
The concept of "intelligence cycle" provides a framework for understanding the definitions, roles, structures and functioning of intelligence services. This article reviews literature based on this framework in depth and elaborates the stages involved in the work of intelligence services: planning, information gathering, selection, analysis, reports and delivery. Each of the stages is presented in a detailed manner, with a special emphasis on analysis, the fourth stage of the investigative process. The intelligence cycle framework is aimed at producing high quality intelligence, which will be valuable for the final user. The goal is to enable the final user to understand security issues in depth.